2019
DOI: 10.1002/jcb.28866
|View full text |Cite
|
Sign up to set email alerts
|

miR‐30e‐5p suppresses cell proliferation and migration in bladder cancer through regulating metadherin

Abstract: Recent studies have suggested that miR‐30e‐5p is dysregulated in several human carcinomas; however, the mechanism of miR‐30e‐5p in bladder cancer (BCa) remains unknown. Here, we confirmed that the expression of miR‐30e‐5p was decreased in human BCa specimens and cell lines by quantitative reverse‐transcription polymerase chain reaction (qRT‐PCR). Upregulation of miR‐30e‐5p decreased the proliferation and migration in T24 and UM‐UC‐3 cells. Metadherin (MTDH) was a potential target for miR‐30e‐5p through bioinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 49 publications
1
19
1
Order By: Relevance
“…Studies have demonstrated that miRNAs has diagnostic and therapeutic values for many cancers [15][16][17]. MiR-30e-5p, which is a newly cancer-related miRNA, plays a pivotal role in the progression of different cancers, such as in non-small cell lung cancer [18], colorectal cancer [19], bladder cancer [20]. However, the functional role of miR-30e-5p in NPC is less reported.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that miRNAs has diagnostic and therapeutic values for many cancers [15][16][17]. MiR-30e-5p, which is a newly cancer-related miRNA, plays a pivotal role in the progression of different cancers, such as in non-small cell lung cancer [18], colorectal cancer [19], bladder cancer [20]. However, the functional role of miR-30e-5p in NPC is less reported.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical significance of miR‐30e‐5p, especially its prognostic value in SCCHN, was a key highlight of our current investigation. As a metastasis suppressor, miR‐30e‐5p has been reported to be downregulated in several malignant carcinomas, such as bladder cancer, colorectal cancer, nasopharyngeal carcinoma and head and neck cancer . In the available clinical studies based on tumor samples, low expression of miR‐30e‐5p always exists in patients with more aggressive clinical characteristics, including advanced TNM stages and metastasis, which is consistent with our conclusion.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the clinical results, loss and gain of functional experiments clearly indicated the critical role of miR‐30e‐5p in SCCHN metastasis. Several studies have confirmed that miR‐30e‐5p is a microRNA that is closely associated with metastasis in vitro; however, how miR‐30e‐5p blocks cancer metastasis and its exact molecular mechanisms remain largely unknown. In the process of metastasis, metastatic cancer cells are required to detach the primary lesion and enhance the migratory and invasive abilities, in which EMT is indispensable in the initiation of metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small non-coding RNA molecules that bind to the 3'-untranslated region (3'UTR) of corresponding messenger RNAs (mRNAs). MiRNAs have been reported to have a potential role as diagnostic biomarkers in ovarian cancer [13], colorectal cancer [14], and pancreatic cancer [15]. In 2016, Zhou et al identified a six-miRNA diagnostic panel that were upregulated in the plasma of patients with adenocarcinoma of the lung in an Asian population [16].…”
Section: Introductionmentioning
confidence: 99%